2017
DOI: 10.1063/1.4986238
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh capacitive energy storage in highly oriented Ba(ZrxTi1-x)O3 thin films prepared by pulsed laser deposition

Abstract: We report structural, optical, temperature and frequency dependent dielectric, and energy storage properties of pulsed laser deposited (100) highly textured BaZr x Ti 1−x O 3 (x=0.3, 0.4 and 0.5) relaxor ferroelectric thin films on La 0.7 Sr 0.3 MnO 3 /MgO substrates which make this compound as a potential lead-free capacitive energy storage material for scalable electronic devices. A high dielectric constant of ~1400-3500 and a low dielectric loss of <0.025 were achieved at 10 kHz for all three compositions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…On the other hand, using PLD, Instan et al fabricated BZT30 thin films, with an ultrahigh J r of 156 J/cm 3 at 3000 kV/cm and an η of ~73%, which is by far one of the highest achieved ED values in relaxor based thin film structures [ 182 ]. Improving this work, Cheng et al published a record high J s and η of up to 166 J/cm 3 and 96% on BZT based films using RF magnetron sputtering.…”
Section: Tuning Energy Density By Processing Methodsmentioning
confidence: 99%
“…On the other hand, using PLD, Instan et al fabricated BZT30 thin films, with an ultrahigh J r of 156 J/cm 3 at 3000 kV/cm and an η of ~73%, which is by far one of the highest achieved ED values in relaxor based thin film structures [ 182 ]. Improving this work, Cheng et al published a record high J s and η of up to 166 J/cm 3 and 96% on BZT based films using RF magnetron sputtering.…”
Section: Tuning Energy Density By Processing Methodsmentioning
confidence: 99%
“…Therefore, energy www.springer.com/journal/40145 storage performances of BZT-based ceramic systems receive more attention. Instan et al [130] prepared 400 nm <100>-oriented Ba(Zr x Ti 1−x )O 3 (x = 0.3, 0.4, 0.5) relaxor ferroelectric thin films using PLD on La 0.7 Sr 0.3 MnO 3 /MgO substrates. Importantly, W rec of all ceramics can reach a scale of 10 2 around E b ≈ 3 MV/cm, and a maximum W rec of 156 J/cm 3 is obtained at x = 0.3 composition.…”
Section: Lead-free Relaxor Ferroelectric Ceramicsmentioning
confidence: 99%
“…In the last decade, new emerging applications in BZT-based compounds such as electrocaloric cooling systems or energy storage capacitors have seen a number of publication soaring [18][19][20][21][22][23][24][25][26]. Asbani et al [18] reported a large electrocaloric responsivity coefficient (ΔT/ΔE) of 0.34 K mm/kV in Ba0.8Ca0.2Zr0.04Ti0.96O3 peaked at 386K.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the energy storage properties in BZT-based ceramics have received also great attention in both bulk [27] and thin-film forms [24][25][26]. It has been shown that these systems have the potential ability to deliver high power density with an ultra-fast chargingdischarging process, promising for advanced electronic applications such as in electric power systems, or in high-frequency inverters and power grids [28,29].…”
Section: Introductionmentioning
confidence: 99%